The Pluralist Economy in Africa: A Study of the Relationship between Economic Complexity and the Life Ladder - (:unkn) unknown (My University, 2023)
This study finds a significant correlation between economic complexity and the life ladder in Africa, using data from the World Development Indicators (2022), World Happiness Report (2023) and Observatory of Economic Complexity (2023) over the period 2000 to 2021. The FGLS estimation method shows that economic complexity has a positive impact on the life ladder of African populations. These findings underscore the importance of governments implementing economic policies that prioritise the strengthening of economic complexity, thereby promoting the life ladder of individuals in Africa. Key measures to achieve this goal include promoting economic diversification, investing in education and training, encouraging entrepreneurship and innovation, promoting regional integration, improving infrastructure and technological accessibility, and establishing robust social protection systems. The adoption and implementation of these policies will be critical to increasing the overall life ladder of Africa's population while promoting sustainable economic development.
Keywords: African Research